Here to stay, here to fight : a Race today anthology - Field, Paul, 1971-; Bunce, R. E. R. (Robin E. R.); Howe, Leila Hassan, 1948-; Peacock, Margaret (Pluto Press, 2019)
A unique anthology of Race Today (1973-88), featuring original contributions from C.L.R. James, Linton Kwesi Johnson and Darcus Howe.